Edible blend films of pectin and poly(ethylene glycol): Preparation and physico-chemical evaluation. (April 2018) - Šešlija, Sanja; Nešić, Aleksandra; Ružić, Jovana; Kalagasidis Krušić, Melina; Veličković, Sava; Avolio, Roberto; Santagata, Gabriella; Malinconico, Mario
Abstract: The aim of this study was the development of novel polysaccharide based films intended to be used as edible food packaging material. The films were prepared by solution casting method using highly methoxylated pectin (PEC) and poly(ethylene glycol) (PEG) of various molecular weights (400, 600 and 1000 gmol -1 ) in different ratios (5:1, 3:1 and 1:1). The film formation was supported by hydrogen bonding between PEC and PEG, which was evidenced by means of ATR-FTIR and NMR analysis. TGA revealed that generally PEG behaves like a pro-degrading agent for pectin, except in the case of PEC/PEG film with a ratio of 1:1. Furthermore, DSC thermograms indicated that PEG1000 exists as a separate phase in the pectin matrix while the formulations with PEG400 and PEG600 showed mainly amorphous morphology. The addition of PEG enhanced the plasticization of PEC films, as evidenced by progressive decreasing of the glass transition temperature values ( T g ). The tensile test measurements showed that increasing concentration of PEG produced weaker and more flexibile films. Due to the increased molecular mobility, the pectin phase became more permeable to water vapor as the PEG concentration increased. The obtained results showed that the combination of both polymers resulted in interesting bio–inspired edible films with the potential to compete with commercially used synthetic package materials. Graphical abstract: Image Highlights: Edible films from pectin and PEG were prepared. Film formation was supported by hydrogen bonding between components. Thermal and mechanical properties were affected by concentration and molecular weight of PEG. The increasing PEG concentration caused an increase in water vapor permeability. Films showed potential to be used in food packaging industry.